Sob a prédica da ordem: a atuação da Companhia de Jesus na Vila de São José de Ribamar do Aquiraz (1723–1759) - Tavares, Ronald Ferreira dos Santos Gomes (2019)
The main purpose of this study is to investigate the role played by the Jesuits in the town of São José de Ribamar, Aquiraz, Brazil, seat of the District of Siará Grande, from 1723 to 1759, including their relations with local society and the various factors that influenced the preference of the place for installation of Siará’s Real Hospício. We chose to work with this space for many reasons that particularize it in comparison with the performance of the Jesuit Order. A large part of its population consisted of officials of the crown applied in the jurisdictional apparatus, so that there was an expressive range of governance agents living with the other actors who composed the colonial society, such as Indians, slaves, mechanical officers, graduates, breeders, farmers, and religious, among others. Thus, the locality has always been a fertile ground for the struggle of the different interests that these groups congregated, which were of interest to the Society of Jesus, since in the urban centres, through contact with society, the Jesuits obtained a favorable scenario to demonstrate their relevance in the colonial daily life, both on the spiritual and temporal levels.